Faktor Pembentuk dari Kemandirian Belajar Siswa - Mulyadi Mulyadi; Abd. Syahid (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2020)
Self-Regulated Learner is a student who can stand alone, not dependent on others. His or her behavior and attitude do not come in sudden but through a process since their childhood. Among individuals are different because of many factors. Factors that greatly influence student's self-regulated attitude categories into two factors from internal and external. Internal factors, namely, physiological factors; including the physical condition of students, healthy or unhealthy, and psychological factors; including talents, interests, attitudes, motivation, intelligence, and others. Meanwhile, external factors; including family, school, and society. This study discussed how good student self-regulated learning, its characteristics, its benefits, and its process.